Phytocannabinoids and Cannabis-Based Products as Alternative Pharmacotherapy in Neurodegenerative Diseases: From Hypothesis to Clinical Practice - Paes-Colli, Yolanda; Aguiar, Andrey F. L.; Isaac, Alinny Rosendo; Ferreira, Bruna K.; Campos, Raquel Maria P.; Trindade, Priscila Martins Pinheiro; de Melo Reis, Ricardo Augusto; Sampaio, Luzia S. (Frontiers in Cellular Neuroscience, 2022)
Historically, Cannabis is one of the first plants to be domesticated and used in medicine, though only in the last years the amount of Cannabis-based products or medicines has increased worldwide. Previous preclinical studies and few published clinical trials have demonstrated the efficacy and safety of Cannabis-based medicines in humans. Indeed, Cannabis-related medicines are used to treat multiple pathological conditions, including neurodegenerative disorders. In clinical practice, Cannabis products have already been introduced to treatment regimens of Alzheimer's disease, Parkinson's disease and Multiple Sclerosis’s patients, and the mechanisms of action behind the reported improvement in the clinical outcome and disease progression are associated with their anti-inflammatory, immunosuppressive, antioxidant and neuroprotective properties, due to the modulation of the endocannabinoid system. In this review, we describe the role played by the endocannabinoid system in the physiopathology of Alzheimer, Parkinson and Multiple Sclerosis, mainly at the neuroimmunological level. We also discuss the evidence for the correlation between phytocannabinoids and their therapeutic effects in these disorders, thus describing the main clinical studies carried out so far on the therapeutic performance of Cannabis-based medicines.